Serum and tissue zinc in epithelial malignancies: a meta-analysis - Gumulec, Jaromir; Masarik, Michal; Adam, Vojtech; Eckschlager, Tomas; Provaznik, Ivo; Kizek, Rene (PloS one, 2014)
BACKGROUND AND OBJECTIVES: Current studies give us inconsistent results regarding the association of neoplasms and zinc(II) serum and tissues concentrations. The results of to-date studies using meta-analysis are summarized in this paper. METHODS: Web of Science (Science citation index expanded), PubMed (Medline), Embase and CENTRAL were searched. Articles were reviewed by two evaluators; quality was assessed by Newcastle-Ottawa scale; meta-analysis was performed including meta-regression and publication bias analysis. RESULTS: Analysis was performed on 114 case control, cohort and cross-sectional studies of 22737 participants. Decreased serum zinc level was found in patients with lung (effect size = -1.04), head and neck (effect size = -1.43), breast (effect size = -0.93), liver (effect size = -2.29), stomach (effect size = -1.59), and prostate (effect size = -1.36) cancers; elevation was not proven in any tumor. More specific zinc patterns are evident at tissue level, showing increase in breast cancer tissue (effect size = 1.80) and decrease in prostatic (effect size = -3.90), liver (effect size = -8.26), lung (effect size = -3.12), and thyroid cancer (effect size = -2.84). The rest of the included tumors brought ambiguous results, both in serum and tissue zinc levels across the studies. The association between zinc level and stage or grade of tumor has not been revealed by meta-regression. CONCLUSION: This study provides evidence on cancer-specific tissue zinc level alteration. Although serum zinc decrease was associated with most tumors mentioned herein, further--prospective--studies are needed.
Keywords: Models, Statistical; nádory; statistické modely; Female; epitel; ženské pohlaví; Humans; mužské pohlaví; Male; lidé; Zinc; zinek; Epithelium; Neoplasms